2005
DOI: 10.1111/j.1469-8986.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Absolute pitch and pupillary response: Effects of timbre and key color

Abstract: The pitch identification performance of absolute pitch possessors has previously been shown to depend on pitch range, key color, and timbre of presented tones. In the present study, the dependence of pitch identification performance on key color and timbre of musical tones was examined by analyzing hit rates, reaction times, and pupillary responses of absolute pitch possessors (n = 9) and nonpossessors (n = 12) during a pitch identification task. Results revealed a significant dependence of pitch identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Following each trial the presentation of a smiley indicated a self paced period were subjects were allowed to blink, a procedure which is known to minimize blinking artifacts during the experimental trial (Schlemmer et al, 2005). The new trial started with the next fixation cross.…”
Section: Methodsmentioning
confidence: 99%
“…Following each trial the presentation of a smiley indicated a self paced period were subjects were allowed to blink, a procedure which is known to minimize blinking artifacts during the experimental trial (Schlemmer et al, 2005). The new trial started with the next fixation cross.…”
Section: Methodsmentioning
confidence: 99%
“…Schlemmer, Kulke, Kuchinke, & Van der Meer, 2005). The task was to name the pitches of the sine waves.…”
Section: Material: Memory and Attention Testsmentioning
confidence: 99%
“…In this sense, it is possible that prior note knowledge might have had a more substantial effect on tone estimates if a more familiar timbre (e.g., piano) note series was used. Previous research indicates that AP possessors are more accurate and faster to identify notes when they are familiar with the timbre (Bahr et al, 2005; Schlemmer et al, 2005). Further Schlemmer (2009) has shown a positive correlation between experience with a particular piece and the ability to spontaneously sing it on key without the aid of a reference tone.…”
Section: Discussionmentioning
confidence: 98%